SKRINING FITOKIMIA DAN AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BATANG (Eusideroxylon zwageri) TERHADAP Escherichia coli DAN Salmonella typhi - Hana Wila; Fathul Yusro; Yeni Mariani (Universitas Tanjungpura, 2018)
Diarrhea and typhoid fever are diseases commonly suffered by people in Indonesia, and bacteria such as Escherichia coli (diarrhea) and Salmonella typhi (typhoid fever) are one of those diseases causative agents. Various plants are potentially used as anti-bacterial including ulin (Eusideroxylon zwageri). The aims of this study were to analysis the yield and potential secondary metabolite content in ethanol extract of E. zwageri, and determine the optimal concentration in inhibits the growth of bacteria E. coli and S. typhi. The methods used in this study were measure the moisture content of E. zwageri wood bark powder, extraction with ethanol solvent, measure the yield percentage, qualitative of phytochemical analysis, and antibacterial assays. The results showed that the yield of ethanol extract of E. zwageri is 21,63% with 7,6% of moisture content. The extract positively contained alkaloids, flavonoids, tannins, saponins, phenolics and terpenoids. The optimum concentration in inhibits the growth of bacteria E. coli is 200 mg/ml and categorized as very strong inhibition response, and 15 mg/ml is concentration used in inhibits the S. typhi and categorized as strong inhibition response.Keywords: Antibacterial activity, Escherichia coli, Eusideroxylon zwageri, phytochemical screening, Salmonella typhi.